Find the Fourier transform of the following signals. (a) x(t) = u(t + 2) + u(t + 1) – u(t – 1) – u(t – 2). (b) x(t) = 2u(t + 2) – u(t + 1) + u(t – 1) – 2u(t – 2). (c) x(t) = {cos (2 pi t), |t| lessthanorequalto 1/2 0 otherwise (d) x(t) = {sin (2 pi t), |t| lessthanorequalto 1/2 0 otherwise (e) x(t) = delta(t + 1)-delta(t-1).

6 2 - Find the Fourier transform of the following signals. (a) x(t) = u(t + 2) + u(t + 1) - u(t - 1) - u(t - 2). (b) x(t) = 2u(t + 2) - u(t + 1) + u(t - 1) - 2u(t - 2). (c) x(t) = {cos (2 pi t), |t| lessthanorequalto 1/2 0 otherwise (d) x(t) = {sin (2 pi t), |t| lessthanorequalto 1/2 0 otherwise (e) x(t) = delta(t + 1)-delta(t-1).

This content is for Premium members only.
sign up for premium and access unlimited solutions for a month at just 5$(not renewed automatically)


images - Find the Fourier transform of the following signals. (a) x(t) = u(t + 2) + u(t + 1) - u(t - 1) - u(t - 2). (b) x(t) = 2u(t + 2) - u(t + 1) + u(t - 1) - 2u(t - 2). (c) x(t) = {cos (2 pi t), |t| lessthanorequalto 1/2 0 otherwise (d) x(t) = {sin (2 pi t), |t| lessthanorequalto 1/2 0 otherwise (e) x(t) = delta(t + 1)-delta(t-1).

already a member please login